Maximising the recovery of low grade heat: An integrated heat integration framework incorporating heat pump intervention for simple and complex factories. (15th December 2015) - Miah, J.H.; Griffiths, A.; McNeill, R.; Poonaji, I.; Martin, R.; Leiser, A.; Morse, S.; Yang, A.; Sadhukhan, J.
Highlights: A new practical heat integration framework incorporating heat pump technology for simple and complex food factories. A decision making procedure was proposed to select process or utility heat integration in complex and diverse factories. New stream classifications proposed to identify and compare streams linked between process and utility, especially waste heat. A range of 'Heat Pump Thresholds' to identify and compare heat pump configurations with steam generation combustion boiler. Abstract: The recovery of heat has long been a key measure to improving energy efficiency and maximising the heat recovery of factories by Pinch analysis. However, a substantial amount of research has been dedicated to conventional heat integration where low grade heat is often ignored. Despite this, the sustainability challenges facing the process manufacturing community are turning interest on low grade energy recovery systems to further advance energy efficiency by technological interventions such as heat pumps. This paper presents a novel heat integration framework incorporating technological interventions for both simple and complex factories to evaluate all possible heat integration opportunities including low grade and waste heat. The key features of the framework include the role of heat pumps to upgrade heat which can significantly enhance energy efficiency; the selection process of heat pump designs which was aided by the development of 'Heat Pump Thresholds' to decide if heat pump designs are cost-competitive with steam generation combustion boiler; a decision making procedure to select process or utility heat integration in complex and diverse factories; and additional stream classifications to identify and separate streams that can be practically integrated. The application of the framework at a modified confectionery factory has yielded four options capable of delivering a total energy reduction of about 32% with an economic payback period of about 5 years. In comparison, conventional direct and/or indirect heat integration without heat pumps showed an energy reduction potential of only 3.7–4.3%. Despite the long payback, the role of heat pumps combined with an integrated search by direct and indirect heat exchange from zonal to factory level can provide the maximum heat recovery. The framework has the potential to be applied across the process manufacturing community to inform longer-term energy integration strategies.